Keyboard - smart card reader controller using VHDL / Mohd Zuwairi Lani - Mohd Zuwairi, Lani (2001)
As the time fly by the technology of computers has improves and much security is needed in every transaction of data that being done. In this project, designing a microcontroller for keyboard and smart card reader terminal integration is being done. At first stage, the architecture of the controller will analyze and studied. This will need some practice of knowledge in computer organization and architecture, as well as microprocessors architecture designs. Then the architecture is design using hardware prototyping. This is by using the VHSIC Hardware Description Language (VHDL). The codes done using the language then being simulate to get the result of a proper working design. The reports will consists of analysis, designs, simulation results and the final outcome of the project which is the microcontroller itself. It will also cover some survey on books, websites and other sources that related to the project. In a way this project is one of many steps in making a better secure protection in the network for the coming future.